Consumers’ purchasing behavior towards food trucks’ products - Burhanuddin, Nur Aina (2018)
Food truck in Malaysia has been brought in the early of 2000 and it is become phenomenal in year 2008 (Eksan et al., 2017). Risvik (2011), purchase decision regarding to the food products are very critical due to the food is becoming as part of human body once we consumed, so the decision of food product and purchase are issue to internal evaluation process.This purpose of this research is to study and understand consumers’ purchasing behavior towards food trucks’ products. Moreover to know more about what is factor contribute to construct the purchasing behavior of consumers towards food trucks products. Also to investigate the most significant factors that influence consumers’ purchasing behavior towards food trucks’ products. Significant of this study is for producers and marketers, consumers, researcher and academians. In this study, the factors used are attitudes, price, brand image, halal awareness, service quality, social influence and trust. The studies have been conducted in Bangi, Serdang and Putrajaya area. The sampling size is 400 respondents is selected to get desired outcomes. A well-structured questionnaire is filled out by consumers around that area. Data is processed in SPSS and the data analysis used are descriptive analysis, factor analysis and multiple regression analysis. Results from factor analysis shows five factors which are attitudes, brand image, halal awareness, social influence, service quality and brand image. After the multiple regression analysis, attitudes, brand image, social influence, service quality and brand image that have significant 1%. From this findings, the retailers of food trucks can focus and improve all these characters that can fulfill consumers’ needs and wants. For future researcher, the area covered can be wider around Malaysia. Consumers are being advice to do research before purchasing the food trucks’ products. Last but not least, food trucks’ vendors can add varieties of the products so they can attract more consumers.